HUBUNGAN KONSUMSI SUPLEMEN DENGAN KEBUGARAN JASMANI PADA LAKI-LAKI DEWASA MEMBER TIVOLI FITNESS CENTER DI SIDOARJO - Fajar Afrindo; Merryana Adriani (Universitas Airlangga, 2019)
Physical fitness is the basic capital of a person to perform physical activities efficiently in a long time without fatigue with adequate rest. Good physical fitness can be very influential on the work activities of respondents, and it is also very important for human life. This study aims to analyze the relationship between consuming supplements and nutritional status on the members of Tivoli fitness center in Sidoarjo. The type of the study used in this study was a quantitative approach with Cross Sectional study. This study employed quantitative approach with cross sectional study where each of the respondents was observed or interviewed for once, and dependent and independent variables were observed or interviewed at the same time or following on observation time status. Further, this study applied simple random sampling with sample list of male member respondents in Tivoli fitness center. Variables in this study were independent variables consisting of respondent characteristic, level of knowledge and consumption pattern, and a dependent variable that was physical fitness. Data analysis was done by using statistic test. The results of this study showed that respondents who consumed more supplementshad higher fitness level in which they felt fitter compared to the respondents who did not consume supplements. The result of chi square statistic test from fisher's exact test obtained p value of 0.716. The p value is > 0.05. It can be concluded from the study that consumption of supplements showed no statistically significant relationship with the physical fitness ofthe members of Tivoli fitness center in Sidoarjo.